2008
DOI: 10.1128/jvi.01405-08
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Protein hnRNP D Modulates Internal Ribosome Entry Site-Dependent Translation of Hepatitis C Virus RNA

Abstract: Hepatitis C virus (HCV), one of the major causative agents of virus-related liver cirrhosis and hepatocellular carcinoma in humans, contains a single-stranded RNA genome of positive polarity. HCV RNA contains nontranslated regions (NTRs) at the 5Ј and 3Ј ends (18,23) and a long open reading frame encoding polyprotein that is synthesized through a single translational initiation event directed by an RNA element designated the internal ribosomal entry site (IRES) (21, 38) at the 5Ј NTR (46). The polyprotein is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 50 publications
(63 reference statements)
4
79
0
Order By: Relevance
“…By binding to defined genomic elements and by modulating viral protein or RNA synthesis, AUF1/hnRNPD was found to accelerate or inhibit the life cycles of various RNA viruses (Paek et al 2008;Lund et al 2012;Cathcart et al 2013;Hino et al 2013;Lin et al 2014). It is quite conceivable that the methylation-enhanced RNA restructuring activity of the AUF1 p45 isoform, which was demonstrated here to support WNV replication, may underlie several of the functions of AUF1 during the replication processes of other viruses as well.…”
Section: Discussionmentioning
confidence: 67%
“…By binding to defined genomic elements and by modulating viral protein or RNA synthesis, AUF1/hnRNPD was found to accelerate or inhibit the life cycles of various RNA viruses (Paek et al 2008;Lund et al 2012;Cathcart et al 2013;Hino et al 2013;Lin et al 2014). It is quite conceivable that the methylation-enhanced RNA restructuring activity of the AUF1 p45 isoform, which was demonstrated here to support WNV replication, may underlie several of the functions of AUF1 during the replication processes of other viruses as well.…”
Section: Discussionmentioning
confidence: 67%
“…La and PCBP2 proteins have been shown to interact with both of the UTRs and link the 5= and 3= ends of the viral genome, facilitating replication (22,23). Other independent studies on RNA binding proteins like hn-RNPD, hnRNPA1, HuR, Unr, hnRNPU, etc., have indicated that they interact with the viral RNA (24)(25)(26)(27). However, the molecular basis of regulation of viral replication by these RBPs remains a mystery.…”
mentioning
confidence: 99%
“…Control or hnRNP Q-specific siRNA-transfected NIH 3T3 cells were treated with cycloheximide (100 g/ml) for 5 min at 37°C and then harvested. Cell extracts were subjected to sucrose gradient analysis, as previously described (9,35). Total RNA of each fraction was purified using TRI reagent (Molecular Research Center) and subjected to real-time PCR analysis for quantification.…”
Section: Methodsmentioning
confidence: 99%